Ecological drivers of taxonomic, functional, and phylogenetic diversity of bryophytes in an oceanic island - Martins, Anabela (2024)
Montane oceanic islands possess unique geographic and ecological attributes, renderingthem valuable for assessing patterns and drivers of alpha and beta taxonomic, functional,and phylogenetic diversity along elevational gradients. Such comparisons of diversityfacets can provide insights into the mechanisms governing community assembly on is-lands. Herein, we aimed to characterize taxonomic, functional, and phylogenetic bryo-phyte diversity on Madeira Island within and across areas at varying elevations. We alsoassessed how these diversity facets for the alpha and beta components relate to ecologi-cal and anthropogenic factors. We estimated and compared alpha and beta taxonomic,functional, and phylogenetic diversity using 80 plots of 0.5 m × 0.5 m across the wholeelevational gradient of the island. We compiled trait databases and supplemented themwith our own observations. Phylogenetic information was sourced from the Moss andLiverwort Tree of Life. To assess the impact of ecological and anthropogenic factors onthe three facets, we applied linear mixed-effects models and generalized dissimilaritymodels to alpha- and beta-diversity matrices, respectively. All facets of diversity ex-hibited strong correlations within both mosses and liverworts, indicating a substantialcongruence when alpha and beta are analyzed separately. The bryophyte groups catego-rized by the growth form demonstrated contrasting patterns, aligning with their distinc-tive ecological requirements. While a mid-elevation peak emerged as a common patternacross the three facets of alpha diversity, beta diversity often displayed the oppositetrend. Although the relative influence of environmental factors varied depending on thediversity facet and bryophyte grouping considered, we found that alpha and beta diver-sity of bryophytes are more influenced by climatic factors and the predominant type ofvegetation than by anthropogenic factors. In the current context of global change, theseresults should be interpreted with caution, but they point to the resilience of bryophytesto survive in relatively well-preserved natural microhabitats within anthropogenic land-scapes. In this study on Madeira Island, we investigated patterns and drivers of alphaand beta taxonomic, functional, and phylogenetic diversity along elevational gradients.We found that alpha and beta diversity of bryophytes are more strongly influenced byclimatic factors and the predominant type of vegetation than by anthropogenic factors.